The Brooklyn Papyrus Snakebite and Medicinal Treatments’ Magico-Religious Context - Wendy Golding (Religions, 2023)
This paper investigates the role of magic and religion in the context of the Brooklyn Papyrus (47.218.48 and 47.218.85) snakebite treatments. It examines the extent to which these two factors are involved in the treatments and how they shed light on the importance of treating the mind and body of the patient. Information regarding the methods and ingredients used in snakebite treatments in ancient Egypt is obtained from the author’s doctoral thesis in which the Brooklyn Papyrus (47.218.48 and 47.218.85) is transliterated and then translated into English and offers a commentary on the text. This translation enabled the author to understand that magic and religion form part of the snakebite treatment process. Investigating the relationship between these two factors and medical treatment ingredients and methods enables one to know that magic and religion are inextricably linked in the role of healing. The role played by magic and religion in these treatments resulted in a holistic form of treatment in the process of attempting to heal the ancient Egyptian snakebite victim and patient.